International comparison of the impact of COVID on adherence with supportive care focused Choosing Wisely recommendations (CWR). Issue 28 (1st October 2022) - Li, Huaqi; Powis, Melanie Lynn; Saldanha, Erick Figueiredo; Riechelmann, Rachel Simoes; Baiad, Abed; Cavalher, Felicia Peterson; Chen, Kevin; Costa, Maria Rita Silva; Hack, Saidah; Mohmand, Zuhal; Nakhla, Peter; Simões, Maria Fernanda Evangelista; et al.
Abstract : 28 Background: The reorganization of cancer care delivery during the COVID pandemic had the potential to catalyze improvement in CWR adherence by reducing provision of low value care to minimize in-person visits and mitigate potential issues with staff and resource shortages. We evaluated the impact of COVID on adherence with CWR for supportive care, relevant to colorectal and anal cancer patients with stage IV disease at Princess Margaret Cancer Centre (PM) in Canada and AC Camargo Cancer Center (AC) in Brazil. Methods: Eligible patients had a new patient consult 02/2020- 12/2020 (COVID) or the same period in 2019 (control). Performance on individual CWR in the 6 months following initial consultation was calculated as the proportion of eligible patients meeting the recommendation. Results: The PM and AC cohorts each consisted of 100 patients; demographic and disease characteristics of COVID and control cohorts were similar within each centre. Marginally fewer patients received surgery during COVID (PM: 38.3 vs 49.1%, p = 0.28; AC: 54.8 vs 55.2%, p = 0.97). At PM, more patients received radiation therapy during COVID (36.2 vs 24.5%, p = 0.21), whereas the opposite occurred at AC (7.1 vs 17.2%, p = 0.14). A higher proportion of both PM and AC patients treated during COVID died within 6 months of initial consult than in 2019 (PM: 10.6 vs 7.5%, p = 0.015; AC: 21.4 vs 8.6%, p = 0.029). Adherence to selected CWR is summarized below; whereby a higher proportion means higher concordance with CWR. Conclusions: There was low overall adherence to CWR across both centers with no significant changes to patterns of care for patients with stage IV disease during the COVID-19 pandemic.CWR PM COVID n(%) PM Controln(%) AC COVID n(%) AC Controln(%) Avoid chemotherapy and instead focus on symptom relief and PC in patients with advanced cancer unlikely to benefit from chemotherapy 17/47 (36.2) 20/53 (37.7) 5/42 (11.9) 8/58 (13.8) Don't delay or avoid PC for patients with metastatic cancer because they are pursuing disease-directed Tx 5/47 (10.6) 8/53 (15.1) 4/42 (9.5) 6/58 (10.3) Don't routinely use extensive locoregional therapy in most cancer situations where there is metastatic disease and minimal symptoms attributable to primary tumour 18/32 (56.3) 19/40 (47.5) 18/39 (46.2) 25/57 (43.9) Don't use white cell stimulating factors for primary prevention of febrile neutropenia for patients with < 20% risk for this complication 31/34 (91.2) 35/38 (92.1) 34/41 (82.9) 43/56 (76.8) Don't give patients starting on a chemotherapy regimen that has low/moderate risk of causing N/V anti-emetic drugs intended for use with a regimen that has high risk of causing N/V 7/34 (20.6) 10/37 (27.0) 2/40 (5.0) 1/55 (1.8) Don't initiate cancer Tx without discussing intent of Tx with patients 38/43 (88.4) 42/46 (91.3) 34/41 (82.9) 51/56 (91.1) Don't delay advance care planning conversations 13/47 (27.7) 19/53 (35.8) 7/42 (16.7) 1/58 (1.7)